Nanopore Sequencing in Blood Diseases: A Wide Range of Opportunities - Minervini, Crescenzio Francesco; Cumbo, Cosimo; Orsini, Paola; Anelli, Luisa; Zagaria, Antonella; Specchia, Giorgina; Albano, Francesco (Frontiers in Genetics, 2020)
The molecular pathogenesis of hematological diseases is often driven by genetic and epigenetic alterations. Next generation sequencing has considerably increased our genomic knowledge of these disorders becoming ever more widespread in clinical practice. In 2012 Oxford Nanopore Technologies (ONT) released the MinION, the first long-read nanopore-based sequencer, overcoming the main limits of short-reads sequences generation. In the last years, several nanopore sequencing approaches have been performed in various "-omic" sciences; this review focuses on the challenge to introduce ONT devices in the hematological field, showing advantages, disadvantages and future perspectives of this technology in the precision medicine era.